Prevalence of Helicobacter pylori infected in the Kirkuk native population and aassociated with serum ferritin and Iron levels/Iraq - Nadia M. Mohammad; Sabah M. Salih (Tikrit Journal of Pure Science, 2019)
An association of Helicobacter pylori and iron deficiency (ID) was conducted in Kirkuk city on 176 patients attending private laboratories in Kirkuk for the period from 1/8/2016  to  1/4/2017, blood sampling and a data collection survey were performed in 176 patients suffering from digestive problems and disorder ,120 of them with H.pylori, serum ferritin and iron were measured by ELISA and direct enzymatic method techniques respectively. the result showed that 67 (55.83%) of the patients have serum ferritin concentrations below the normal range indicating iron deficiency, 69 (57.5%) of the patients have iron concentrations below the normal range indicating iron deficiency.